Improvement of growth, yield and associated bacteriome of rice by the application of probiotic Paraburkholderia and Delftia - Islam, Tofazzal; Fatema,; Hoque, M. Nazmul; Gupta, Dipali Rani; Mahmud, Nur Uddin; Sakif, Tahsin Islam; Sharpe, Andrew G. (Frontiers in Microbiology, 2023)
Paraburkholderia fungorum strain BRRh-4 and Delftia sp. strain BTL-M2 promote the growth and yield of plants. This study aimed to assess the effect of BRRh-4 and BTL-M2 application on growth, yield, and bacteriome in roots and rhizosphere soil of rice under varying doses of N, P, and K fertilizers. Application of BRRh-4 and BTL-M2 strains significantly (p < 0.05) increased seed germination, growth, and yield of rice compared to untreated control. Interestingly, the grain yield of rice by these bacteria with 50% less of the recommended doses of N, P, and K fertilizers were statistically similar to or better than the rice plants treated with 100% doses of these fertilizers. Targeted amplicon (16S rRNA) sequence-based analysis revealed significant differences (PERMANOVA, p = 0.00035) in alpha-diversity between the root (R) and rhizosphere soil (S) samples, showing higher diversity in the microbial ecosystem of root samples. Additionally, the bacteriome diversity in the root of rice plants that received both probiotic bacteria and chemical fertilizers was significantly higher (PERMANOVA, p = 0.0312) compared to the rice plants treated with fertilizers only. Out of 185 bacterial genera detected, Prevotella, an anaerobic and Gram-negative bacterium, was found to be the predominant genus in both rhizosphere soil and root metagenomes. However, the relative abundance of Prevotella remained two-fold higher in the rhizosphere soil metagenome (52.02%) than in the root metagenome (25.04%). The other predominant bacterial genera detected in the rice root metagenome were Bacillus (11.07%), Planctomyces (4.06%), Faecalibacterium (3.91%), Deinococcus (2.97%), Bacteroides (2.61%), and Chryseobacterium (2.30%). On the other hand, rhizosphere soil metagenome had Bacteroides (12.38%), Faecalibacterium (9.50%), Vibrio (5.94%), Roseomonas (3.40%), and Delftia (3.02%), Taken together, our results indicate that improvement of growth and yield of rice by P. fungorum strain BRRh-4 and Delftia sp. strain BTL-M2 is likely linked with modulation of diversity, structures, and signature of bacteriome in roots and rhizosphere soils. This study for the first time demonstrated that the application of two plant growth-promoting bacteria significantly improves growth, and yield and increases the diversity of the bacterial community in rice.